Prognosis and Concurrent Genomic Alterations in Patients With Advanced NSCLC Harboring MET Amplification or MET Exon 14 Skipping Mutation Treated With MET Inhibitor: A Retrospective Study - Liu, Li; Kalyani, Farhin Shaheed; Yang, Haiyan; Zhou, Chunhua; Xiong, Yi; Zhu, Songlin; Yang, Nong; Qu, Jingjing (Frontiers in Oncology, 2021)
Background: MET amplification or METex14 skipping mutations are uncommon oncogenic events in NSCLC patients. Clinicopathological characteristics, concurrent gene alterations, and prognosis of MET TKIs in these patients are yet to be elucidated. Methods: We retrospectively analyzed the genomic profiles of 43 MET amplifications or 31 METex14 skipping mutations in NSCLC patients with no previous treatment with EGFR TKIs. Survival outcomes were analyzed in evaluable patients receiving MET TKI treatment: MET amplification cohort (n=29) and METex14 skipping mutation cohort (n=29). Results: Among evaluable patients, a shorter PFS was observed in the MET amplification cohort than in the METex14 skipping mutation cohort (7.0 months vs. 11.0 months, P=0.043). Concurrent mutations in both cohorts resulted in a statistically significant shorter PFS (MET amplification: 3.5 months versus 8.0 months, P=0.038, METex14 skipping mutation: 7.0 versus NR months, P=0.022). However, a statistically significant OS (17.0 months versus 20.0 months, P=0.044) was only observed in the MET amplification cohort. TP53, the most common concurrent mutation in both cohorts, was associated with worse survival outcomes as compared to the wild type. The MET amplification cohort with a concurrent PIK3CA mutation exhibited primary resistance to MET TKIs and showed disease progression (80%). Conclusion: MET TKIs could be a better treatment option for patients with METex14 skipping mutations. Concurrent mutations may deteriorate the PFS of MET TKIs in NSCLC patients with MET amplification or METex14 skipping mutations. PIK3CA mutations may confer primary resistance to MET TKIs in patients with MET amplification.